The Effect of Distribution on Product Temperature Profile in Thermally Insulated Containers for Express Shipments. (20th June 2012) - Singh, Jay; Jaggia, Sanjiv; Saha, Koushik
<x xml:space="preserve">Abstract</x> An uninterrupted cold chain is a continual series of storage and distribution activities that maintain a specific temperature or temperature range. Cold chain solutions typically involve excessive packaging to ensure that the desired product temperature is maintained through the distribution process, thereby increasing the logistics‐related costs. There is a myriad of solutions available for shipping temperature‐sensitive products, including those constructed with a variety of packaging materials as well as refrigerants. Although static characteristics for thermally insulated packaging solutions such as the R‐values of package systems as well as the melting points and heat absorption rates of various refrigerants have been studied in the past, none of the past studies have evaluated the effect of comprehensive distribution on the reliability of the cold chain packaging solutions. This research was undertaken to study the temperature profiles for factors such as different densities for a given thickness of thermally insulating material, wall thicknesses and distribution environments for four different types of materials—polyurethane, virgin expanded polystyrene, recycled content expanded polystyrene and vacuum‐insulated panels. The temperature range of 2 °C–8 °C, critical for pharmaceutical drugs and vaccines, was targeted. An interesting regression‐based finding was that the interaction between the R‐value and the wall thickness significantly influenced the length of time the thermally insulated packages stayed in the desired range of 2 °C–8 °C . The findings of this study will be decisive in designing cost‐efficient and practical single‐use cold chain transportation solutions for temperature‐sensitive products. Copyright © 2012 John Wiley & Sons, Ltd.